2020
DOI: 10.1007/s40843-020-1292-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen vacancies-rich cobalt-doped NiMoO4 nanosheets for high energy density and stable aqueous Ni-Zn battery

Abstract: The enhancement of energy density and cycling stability is in urgent need for the widespread applications of aqueous rechargeable Ni-Zn batteries. Herein, a facile strategy has been employed to construct hierarchical Co-doped Ni-MoO 4 nanosheets as the cathode for high-performance Ni-Zn battery. Benefiting from the merits of substantially improved electrical conductivity and increased concentration of oxygen vacancies, the NiMoO 4 with 15% cobalt doping (denoted as CNMO-15) displays the best capacity of 361.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…In addition, owing to the various oxidation states and competitive electrical conductivity, bimetallic oxide, such as, NiMn x O y , [ 312 ] NiMoO 4 , [ 313 ] and NiCo 2 O 4 , [ 314 ] have attracted great attention in Ni‐based aqueous batteries. Shen et al.…”
Section: Cathode For Nickel‐based Aqueous Batteriesmentioning
confidence: 99%
“…In addition, owing to the various oxidation states and competitive electrical conductivity, bimetallic oxide, such as, NiMn x O y , [ 312 ] NiMoO 4 , [ 313 ] and NiCo 2 O 4 , [ 314 ] have attracted great attention in Ni‐based aqueous batteries. Shen et al.…”
Section: Cathode For Nickel‐based Aqueous Batteriesmentioning
confidence: 99%
“…Therefore, metal oxides are more used for electrode materials than conductive polymers [16]. Among many metal oxides, spinel-structured materials have received great attention in recent years, such as NiCo-LDH [14] MnCo 2 O 4 [17,18], ZnMn 2 O 4 [19] , CuCo 2 O 4 [20], NiMoO 4 [21][22][23], and NiCo 2 O 4 /CeO 2 [24]. The jail's team prepared the hexagonal NiCo 2 O 4 nanostructures, and the NiCo 2 O 4 nanostructures exhibited good electrochemical performance with a maximum specific capacitance of 254.1 mAh g −1 at a current density of 1 A g −1 [1].…”
Section: Introductionmentioning
confidence: 99%
“…So far, a large number of advanced cathode materials, such as Ni(OH) 2 , Co 3 O 4 , NiO, Ni-Co LDH, NiCo 2 O 4 , and NiMoO 4 , have been reported. [15][16][17][18][19][20][21][22][23][24] For example, Lu and coworkers demonstrated that the performance of NiCo 2 O 4 nanosheets was greatly enhanced by oxygen-vacancies and surface phosphate ion modulation. 19 Chen and coworkers reported F doped Ni/Co hydroxides/oxides/phosphides as the cathode materials and the effect of anion substitution was deeply investigated.…”
Section: Introductionmentioning
confidence: 99%